REVIEW OF SALES AND INVENTORY ACCOUNTING INFORMATION SYSTEMS - Harlina Liong (Program Pascasarjana STIE Amkop Makassar, 2020)
The results of this study indicate that the sales and inventory accounting information system at the Chir Chir Fusion Chicken Factory Makassar still uses a manual system. The related functions in the sales and inventory accounting information system are waitrees, cooks, cashiers, financial admin, purchasing, cook, financial admin. The documents used in the sales and inventory accounting system are order notes, struck sales, purchase notes. The notes used in the sales and inventory accounting information system are sales records, and stock cards. The sales accounting information system procedure starts from the recording process of sales for inventory is a sales procedure that reduces inventory and purchases that add to the inventory. Keywords: Sales and Inventory Accounting Information Systems